Mediating Role of Brand Perceived Quality in The Effect of Halal Label and Certification on Purchase Intention - Isnawati; Rahyuniati Setiawan; Lindayani (Manunggal Halim Jaya, 2026)
Halal Food Product Purchase Intention refers to consumers' intention to repurchase products that are certified as halal, thereby fostering trust in the product and its authenticity. The food industry, as a sector susceptible to halal issues, is expected to fully comply with halal standards, particularly as global demand for halal-certified products continues to rise in tandem with the growth of the Muslim population and increasing awareness of halal assurance. One popular culinary product in Garut, Mie Jebew Teh Emil, serves as the object of this study. The purpose of this research is to analyze the influence of halal labels and halal certification on halal food purchase intention, both directly and indirectly through the mediating variable of halal brand perceived quality. This study employs a quantitative method by distributing questionnaires to 400 respondents through both online and offline means. The instrument used is a Likert-scale questionnaire designed to measure respondents' perceptions of each variable. Data analysis was conducted using the Structural Equation Modeling (SEM) approach to test the causal relationships among variables. The findings indicate that halal labels and halal certification have a significant influence on halal food purchase intentions, both directly and indirectly through the mediating role of perceived halal brand quality. Moreover, the perceived quality of halal brands also shows a significant effect on consumers' purchase intentions toward halal products. These results were tested at a 95% significance level, leading to the conclusion that trust in halal brand quality plays a significant role in increasing consumers' willingness to purchase halal food products.